A methodology for assessing the feasibility of producing components by flow forming. Issue 1 (1st January 2017) - Marini, Daniele; Corney, Jonathan
Abstract: This paper describes a methodology for assessing the applicability of the flow forming process for the manufacture of specific components. The process starts by filtering potential candidates for flow forming from a component collection and then carries out a detailed assessment of quantitative, technological and economic feasibility before determining a viable process plan. The process described uses analytical relationships and criteria drawn from the literature. For example, qualitative feasibility is evaluated using analytical relationships for ultimate strength prediction. Similarly technological validation is done estimating forming process forces and defects rate which are evaluated against threshold values. A process time model is used to develop a hybrid cost model in order to evaluate economic feasibility. Using these calculated values production feasibilities are established by comparison with reported reduction ratios and process parameters. The paper concluded with a brief summary of the results of applying the process to an industrial case study.